APLIKASI SISTEM LAYANAN PEMESANAN JASA DESAIN DAN APLIKASI BERBASIS ABDROID PADA PT. PUTRA WISANGGENI SATU MENGGUNAKAN METODE WATERFALL - Misbakhul Munir, Misbakhul Munir (LPPM ITB Yadika Pasuruan, 2023)
PT. Putra Wisanggeni Satu is a company that is active in the field of digital platforms, business and trade consultants in the company. Almost all service ordering activities use WhatsApp messenger. revisions are in demand and vulnerable to conversation data being lost or accidentally deleted. The aim of this research is to design and build an Android-based application for ordering design services and applications to improve service quality and make it easier to order services more efficiently. This research involves several steps, including problem analysis, data collection, application design and development and application testing. At the data collection stage, it was carried out using interview and observation methods and for the system development method using the waterfall method. At the application testing stage, the blackbox testing method shows that almost all features are implemented successfully and function properly as well as the results of usability testing, on the Effectiveness aspect of 94.2%, Efficiency aspect of 0.163 goals / Sec with an overall relative efficiency value of 83.3%. And for the satisfaction aspect of 78.5 . The results of this study indicate that the application can view service price lists, place service orders, service revisions and pay by bank transfer method.